Evaluation of hearing results in Behçet's disease - Bayraktar, Cem; Yağız Aghayarov, Özlem; Doğan, Sedat; Işık Bayraktar, Demet; Altuntaş, Ahmet (The European Research Journal, 2019)
Objectives: Behçet's disease is an inflammatory rheumatic disease with recurrent scarring in the oral and genital area, as well as skin, eye, joint, vein, and nerve involvement. The aim of the study was to investigate the level of hearing in Behçet’s disease and whether there is a change in hearing levels as the level of the disease increases.Methods: In this study we examined 32 patients with Behçet’s disease and 50 healthy volunteers. All patients were evaluated with audiometry, tympanometry and acoustic reflex tests, as well as detailed ear, nose, and throat examinations. Results: Sensorineural hearing loss was observed in 9.3% of the patients with Behçet's disease, according to the audiological data, and all patients were bilateral. We also observed sensorineural hearing loss to be the fifth most common symptom in our study. Especially in high frequencies, there was positive correlation between hearing levels and disease exposure time (p < 0.05).Conclusions: We think that the audiological examinations should be included in the routine check-ups of Behçet's patients. In addition, a follow-up assessment of the hearing level of these patients with high frequency audiometry may be more meaningful.